Left atrial function in cardiac amyloidosis. Issue 2 (February 2016) - Di Bella, Gianluca; Minutoli, Fabio; Madaffari, Antonio; Mazzeo, Anna; Russo, Massimo; Donato, Rocco; Zito, Concetta; Aquaro, Giovanni D.; Piccione, Maurizio Cusmà; Pedri, Stefano; Vita, Giuseppe; Pingitore, Alessandro; et al.
Abstract : Aims: Left atrium can be involved by amyloid deposition in familial amyloid polyneuropathy (FAP). The aim of our study is to assess left atrium function in atrial amyloidosis. Methods: Twenty-eight FAP patients (53 ± 12 years) and a control group of 22 asymptomatic individuals (49 ± 11 years) underwent strain echocardiography and cardiac magnetic resonance (CMR). CMR by late gadolinium enhancement (LGE) was used to assess the left atrium amyloid deposition, whereas strain echocardiography was used to quantify the left atrium deformation. The following atrial longitudinal strain (ALS) parameters were assessed: peak at the end of ventricular systole (peak-ALS), peak at early diastole (early-ALS), negative peak in late diastole, precontraction (prec)-ALS (difference between peak-ALS and early-ALS), and late ALS (sum of negative peak and prec-ALS). Results: CMR showed atrial LGE in 14 FAP patients (LGE-atrial group), whereas 14 FAP patients showed no LGE (no-LGE-atrial group). Peak-ALS was significantly lower in the LGE-atrial group (22.8 ± 13%) compared with the no-LGE-atrial group (59.6 ± 33.1%; P  = 0.001) and controls (47.4 ± 16.4%; P  = 0.001). Early-ALS was lower in the LGE-atrial group (10.2 ± 6.2%) compared with the controls (26.3 ± 11.9%; P  = 0.02) and the no-LGE-atrial group (30.2 ± 22.4%; P  = 0.01). Prec-ALS was lower ( P  = 0.001) in the LGE-atrial group (12.6 ± 7.8%) compared with the no-LGE-atrial group (26.2 ± 15%). Conversely, late-ALS was higher ( P  = 0.04) in the no-LGE-atrial group (22.8 ± 12.3%) compared with the controls (13.9 ± 9%); no significant differences were found in the negative peak among groups. Conclusions: Patients with atrial amyloidosis have an adverse left atrium remodeling associated with left atrium dysfunction. Left atrium assessment may provide useful information in the clinical and prognostic stratification of amyloidotic patients.